2015
DOI: 10.1016/j.pmrj.2015.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress After Orthopedic Trauma: Prevalence in Patients and Implications for Rehabilitation

Abstract: Orthopedic trauma is an unforeseen life-changing event. Serious injuries include multiple fractures and amputation. Physical rehabilitation has traditionally focused on addressing functional deficits after traumatic injury, but important psychological factors also can dramatically affect acute and long-term recovery. This review presents the effects of orthopedic trauma on psychological distress, potential interventions for distress reduction after trauma, and implications for participation in rehabilitation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
106
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 77 publications
2
106
0
1
Order By: Relevance
“…The incidence of NI in PICU during the study period proved to be 22.8%, similar to reports from other studies done in PICUs ranging from 22.2% -29.7% [20][21][22]. The data are also similar to other studies done in adult ICUs as reported in the study EPIC of 20.6% [23], but higher than data reported by NNIS of 6.1% or 14.1 / 1000 patient-days or other studies in Europe, where the incidence varies from 6.1-10.2% [24,25]. According to WHO NI incidence in countries with limited sources or low and medium income, it varies from 4.4% -88.9% [26].…”
Section: Discussionsupporting
confidence: 90%
“…The incidence of NI in PICU during the study period proved to be 22.8%, similar to reports from other studies done in PICUs ranging from 22.2% -29.7% [20][21][22]. The data are also similar to other studies done in adult ICUs as reported in the study EPIC of 20.6% [23], but higher than data reported by NNIS of 6.1% or 14.1 / 1000 patient-days or other studies in Europe, where the incidence varies from 6.1-10.2% [24,25]. According to WHO NI incidence in countries with limited sources or low and medium income, it varies from 4.4% -88.9% [26].…”
Section: Discussionsupporting
confidence: 90%
“…Over the course of the reported weeks, her condition improved continuously (Online Supplemental Tables 1 and 3, Online Supplemental Material; www.karger.com/?DOI=487768 ). Considering her traumatic history and the distress she presented with at the beginning of her outpatient rehabilitation, the patient was originally at risk of an unfavorable rehabilitation course [37,38,39]. Given the multimodal setting and the singularity of this case, it remains unclear whether some of this success can be attributed to WATSU.…”
Section: Discussionmentioning
confidence: 99%
“…She was also alert towards signs of inflammation and competent to advise the patient on how to proceed when they augmented. Due to the generous time frame of a WATSU setting and the extensive training of its providers, traumatic emotional contents - which regularly occur in the aftermath of severe physical trauma [37] - can be processed in a constructive spirit, as was exemplified in this case. Technically, aquatic exercise could have been part of this patient's regular physiotherapy during rehabilitation [40]; however, the lack of a hydrotherapy pool, open wounds that cannot be covered, or - as in this case - elevated inflammation markers can easily impede this.…”
Section: Discussionmentioning
confidence: 99%
“…In fact the person suffered of a severe trauma involving his/her safety; Often during the clinical interview the patients report bad and intrusive memories about the trauma and the amputation event; It can also be noted an introverted behavior respect to the relationship with others in order to avoid situation that are related to the traumatic event. The PTSD in amputees is described in many studies regarding veterans [22] and people who suffered of an orthopedic trauma [23], but it has never been considered inside the rehabilitation program.…”
Section: Discussionmentioning
confidence: 99%